Interdependent roles of BRCA1, CtBP, estrogen, and NADH/NAD+ ratio in error-prone repair, breast cancer initiation, and metastasis - Utkarsh Tripathi; Raghvendra Singh (Molecular Biology Reports, 2026)

Exploring biomarkers for keratoconus: current insights and future directions - Deeksha Nautiyal; Smriti Gaba; Utkarsh Jain (Molecular Biology Reports, 2026)

Breaking the permeability-selectivity-fouling trade-off: Electroconductive PES-LIG-GO composite membrane with integrated passive and active biofouling control - Kritika Jashrapuria; Utkarsh Misra; Pawan Kumar; Swatantra P. Singh (Chemical Engineering Journal, 2026)

Expanding the boundaries of bioelectricity and waste management: From natural exoelectrogens to engineered microbial platforms - Nishtha Sah; Rachan Karmakar; Utkarsh Jain; Nidhi Chauhan (Chemical Engineering Journal, 2026)

Global metallogeny, extraction challenges, and exploration pathways of the critical metal Vanadium - Muduru Lachhana Dora; Ravi Kumar Umrao; M. Santosh; Utkarsh Singh; Vindhyavasini Yadav; Cheng-Xue Yang; Mrinal Kanti Mukherjee; Siddhartha Karmakar; Kirtikumar Randive (Ore and Energy Resource Geology, 2026)

Rice sheath rot: An emerging global threat — will biocontrol-driven omics be the gamechanger - Shraddha Bhaskar Sawant; Repudi Shalem Raju; S.R. Prabhukarthikeyan; Devanshu Dev; Prachi Singh; Debasis Mitra; Priya Bhargava; Abhijeet Ghatak; Utkarsh Chaturvedi; Manoj Kumar Yadav; Sudha Nandni; Anil Kumar Singh (Physiological and Molecular Plant Pathology, 2026)

Optimization of biogas yield from organic waste using pongamia pinnata seed shell as bio-additive through integrated experimental and statistical analysis - Utkarsh Baranwal; Shubham More; Ashootosh Mandpe (Bioresource Technology Reports, 2026)

A Multiscale Reliability Framework Combining Surrogate Models and Bayesian Networks for a Deep-Water Subsea Separation System - Utkarsh Bhardwaj (Journal of Marine Science and Engineering, 2026)
Reliability assessments of subsea systems are generally performed at two levels: structural reliability analysis of individual components and functional reliability analysis of the overall system using generic failure-rate databases. This study develops a component-to-system multi-scale framework that integrates these two levels for a subsea separation system operating at 3000 m water depth. At the component level, a Gaussian process regression (GPR) surrogate is developed from 474 finite element simulations of a vertical gravity separator. First-order reliability method (FORM) and Monte Carlo simulation (MCS) are then employed to assess the structural reliability, followed by a time-variant reliability analysis that accounts for corrosion effects. At the system level, the structural reliability model is integrated with functional failure rates through a Bayesian network that considers five equipment items and relevant risk-influencing factors. The surrogate model accurately predicts collapse pressure with an R2 value of 0.996. The intact separator achieves a reliability index of 4.55, satisfying the DNV high-safety-class target, with the structural failure mode contributing only 0.0034% of the separator failure rate. Under a corrosion rate of 0.4 mm/year, the reliability index decreases to 3.12 over a 25-year service period. The structural failure rate crosses the DNV medium-safety-class target of 10−4 per year at year 12, increasing the structural contribution to the overall system failure frequency to 0.33%. Sensitivity analysis indicates that initial ovality and wall thickness are the most influential parameters affecting structural reliability and should therefore be prioritized in design and integrity management strategies. The framework is demonstrated on this physics-consistent dataset; validation against independent nonlinear finite element analyses and experimental collapse data is identified as the necessary next step before the results are used for design.

Professor Madhav Gadgil (1942–2026): people in heart, environment in focus - Yogesh V. Gokhale; Utkarsh Ghate; Shonil Bhagwat; Vijay Edlabadkar; Anirban Ganguly; K. A. Subramanian; Ankur Patwardhan; Gurudas Nulkar; Krushnamegh Kunte (Tropical Ecology, 2026)

Five decades of fertilization: Impacts of mineral and organic inputs on soybean–wheat productivity and sustainability in the Indian Himalayan agroecosystem - Rajendra Prasad Meena; Vijay Singh Meena; Manoj Parihar; Utkarsh Kumar; Priyanka Khati; Amit Kumar; Mangal Deep Tuti; P.K. Mishra; S.C. Pandey; Tilak Mondal; Dibakar Mahanta; Ved Prakash; et al. (Field Crops Research, 2026)

What’s at the back door? Characterising thrift textile donations and their circular potential in the Canadian context - Teagan E. Sterling; Rachel H. McQueen; Anika Kozlowski; Utkarsh Sharma; Kelvin Tsun Wai Ng (Waste Management, 2026)

Precision forecasting of cloudbursts with CNNs and GAF for real-time disaster response - Shirshendu Layek; Megha Bhushan; Shrey Mall; Satyam Vyas; Ugersain Singh; Utkarsh Mahadeo Khaire (Modeling Earth Systems and Environment, 2026)

Effects of long-term sire based genetic upgrading on growth performance of sheep in semi-arid production systems - Harideep Verma; Madan Singh; Shruti; Uttam Kumar Sahu; Utkarsh Verma (Small Ruminant Research, 2026)

Influence of calcium-chelating salts on mineral-equilibria and techno-functional properties of buffalo milk - Mamta Vaishnav; Sumit Arora; Richa Singh; Shaik Abdul Hussain; Vivek Sharma; Utkarsh Deshmukh (International Dairy Journal, 2026)

Genome-based reclassification of Chromohalobacter japonicus Sánchez-Porro et al. 2007 as a later heterotypic synonym of Chromohalobacter beijerinckii Peçonek et al. 2006 - Preeti Yadav; Pooja; Abhilash Kumar; Princy Hira; Gauri Garg; Charu Dogra Rawat; Rup Lal; Utkarsh Sood (Antonie van Leeuwenhoek, 2026)

Experimental and numerical study on the four-point bending behaviour of small-scale steel pipes with dents - Utkarsh Bhardwaj; Baiqiao Chen; C. Guedes Soares (Ocean Engineering, 2026)

Existing gaps in understanding Sustainable Development Goals interactions: Insights from a systematic review - Utkarsh Ashok Khot; Anne Warchold; Prajal Pradhan (Environmental Impact Assessment Review, 2026)

A Bayesian network framework for evidence-based risk analysis of offshore wind turbines - Utkarsh Bhardwaj; C. Guedes Soares (Ocean Engineering, 2026)

Spatiotemporal dynamics of moisture influx and their role in precipitation extremes: A study of December 2023 in Kayalpattinam - Sree Anusha Ganapathiraju; Utkarsh Kanth; Madhuri Sai Latha V.; Maheswaran Rathinasamy; Niranjan Kumar Kondapalli; Sara M. Vallejo-Bernal; Norbert Marwan; Sukhwinder Kaur (Atmospheric Research, 2026)

Lantana camara L. invasions alter belowground microbial symbiotic network and soil physicochemical characteristics, thereby inhibiting the growth of a native plant Ocimum sanctum L. - Pooja Shukla; Deepak Kumar; Utkarsh Talukdar; Gaurav Pal; Kanchan Kumar; Raghvendra Singh; Satish K. Verma (Symbiosis, 2026)

Microplastic contamination and health risk assessment in economically important freshwater fish (Labeo rohita and Channa punctatus) from the Pawna River, India - Amol Shivaji Mali; Shailesh Ghodake; Utkarsh Maheshwari; Kirti Zare; Atul Kolhe; Pravin Gorde; Mayur Jagtap; Sandip Nehe (Food Bioscience, 2025)

Evaluating recent developments in utilizing organic waste for biofuel production - A comprehensive review - Utkarsh Baranwal; Ashootosh Mandpe (Biomass and Bioenergy, 2025)

Quantitative Laser Diffraction Mediated Detection of Submicron and Subvisible Aggregates (100 nm–10 μm) in Biotherapeutics: Need for Regulatory Attention To this Neglected Particle Size Range - Utkarsh Tathe; Aswani Kancherla; Prajakta Dandekar; Ratnesh Jain (Journal of Pharmaceutical Innovation, 2025)

Respiratory health impacts of opencast coal mining in India: an epidemiological study - Vara Prasad Kasa; Biswajit Samal; Chaitanya Mittal; Brajesh Kumar Dubey; Sujay Das; Suresh Kumar Sahu; Mahesh Pujari; Swagatika Swain; Suneetha Jagu; Utkarsh Tripathi (Air Quality, Atmosphere & Health, 2025)

Environmental and socio-economic Pareto-front trade-off analysis of U.S. PET packaging material in a circular economy - Utkarsh S. Chaudhari; David W. Watkins; Robert M. Handler; Barbara K. Reck; Anne T. Johnson; Tasmin Hossain; Damon S. Hartley; Vicki S. Thompson; David R. Shonnard (Sustainable Production and Consumption, 2025)

Performance analysis of solar still using 10-E, sustainability, and heat transfer analysis: Exploring synergistic effects of PCM quantity and ultrasonic fogger - Jay R. Patel; Utkarsh Shrivastava; Y. Naresh; J. Banerjee (Desalination, 2025)

Evaluation of synergistic anti-inflammatory activity of selected natural products in combination with teriflunomide in LPS stimulated RAW 264.7 cells for rheumatoid arthritis treatment - Sriravali Karnam; Utkarsh Jagtap; Anil B. Jindal; Atish T. Paul (South African Journal of Botany, 2025)

Designing a deep learning-based framework for the prediction of lake surface closed curves - Celso Augusto Guimarães Santos; Debasmita Misra; Sophia Ghanimeh; Adeyemi Olusola; Utkarsh Patel; Golmar Golmohammadi; Erfan Abdi; Vahid Karimi; Mohammad Ali Ghorbani (Earth Science Informatics, 2025)

Exploring land surface temperature (LST) and spectral signatures of Baratang and Diglipur mud volcanoes using ASTER VNIR-SWIR-TIR bands in the Andaman and Nicobar Islands, India - Komal Rani; Pawan Dewangan; Sriram Gullapalli; Priyanka Mary Dorepalli; Utkarsh Umesh Gaonkar (Advances in Space Research, 2025)

Advancing Sustainable Crop Yield Enhancement through Environmentally Friendly Nanoparticle Synthesis: A Comprehensive Review - Anjali Bharti; Vinita Hooda; Amarpal Singh; Ramesh Namdeo Pudake; Utkarsh Jain; Nidhi Chauhan (Journal of Soil Science and Plant Nutrition, 2025)

Computational Insights into Antioxidant Enzymes and Metalloproteins of Tetmemena sp. SeJ-2015 (Spirotrichea; Ciliophora) in Combating Heavy Metal Stress - Sripoorna Somasundaram; Jeeva Susan Abraham; Swati Maurya; Utkarsh Sood; Rup Lal; Seema Makhija; Ravi Toteja (Indian Journal of Microbiology, 2025)

Impact of Exercise-Induced Muscle Damage on Balance: A Systematic Review and Meta-Analysis - Niloofar Fakhraei Rad; Utkarsh Singh; Kenji Doma (Journal of Science in Sport and Exercise, 2025)

Estimating Water Levels through Smartphone-Imaged Gauges: A Comparative Analysis of ANN, DL, and CNN Models - Celso Augusto Guimarães Santos; Mohammad Ali Ghorbani; Erfan Abdi; Utkarsh Patel; Siria Sadeddin (Water Resources Management, 2025)

Nanomaterial Modified Screen Printed Electrode Based Electrochemical Genosensor for Efficient Detection of Neonatal Sepsis - Neha Gopal; Nidhi Chauhan; Utkarsh Jain; Sujata K. Dass; Ramesh Chandra (Indian Journal of Microbiology, 2025)

Polyphasic characterization of 15 heterocytous cyanobacterial isolates from different habitats of India and description of 9 novel species belonging to the genera Desikacharya, Aliinostoc, and Desmonostoc - Sagarika Pal; Aniket Saraf; Naresh Kumar; Harsh Pant; Shaikh Soyeb Akhatar Badruddin; Shaikh Maksood Ali Sajibulla; Shaikh Kalamuddin Nijamuddin; Ambika Prajapati; Utkarsh Talukdar; Niraj Kohar; Arush Singh; Pampi Sarmah; et al. (Algal Research, 2025)

Analyzing the performance of deep convolutional neural network models for weed identification in potato fields - Rajni Goyal; Amar Nath; Utkarsh Niranjan; Rakesh Sharda (Crop Protection, 2025)

Weed detection using deep learning in complex and highly occluded potato field environment - Rajni Goyal; Amar Nath; Utkarsh Niranjan (Crop Protection, 2025)

Biodetection Strategies for Selective Identification of Candidiasis - Riya Verma; Smriti Gaba; Nidhi Chauhan; Ramesh Chandra; Utkarsh Jain (Indian Journal of Microbiology, 2024)

Ti3C2 (MXene), an advanced carrier system: role in photothermal, photoacoustic, enhanced drugs delivery and biological activity in cancer therapy - Vishal Kumar Deb; Utkarsh Jain (Drug Delivery and Translational Research, 2024)

Flexible transparent conductors with a percolated Ag nanostructure and its application as efficient self-bias plasmonic photodetector - Sobhan Hazra; Sandeep Dahiya; Satya Veer Singh; Utkarsh Pandey; Swati Suman; Parasuraman Swaminathan; Bhola Nath Pal (Chemical Engineering Journal, 2024)

Sustainable Development of Functionalized Cobalt Oxide Nanoparticles with Effective Cu(II) Sorbent Properties - Saswat Kumar Pradhan; Vikram Pareek; K. Anil Kumar; Utkarsh Maheshwari; Jitendra Panwar; Suresh Gupta (Water, Air, & Soil Pollution, 2024)

Geoheritage of Charaideo Moidams (Assam, India): a Tale of Human Resilience and Man-Environment Relationship - Archana Das; K. C. Nauriyal; S. P. Prizomwala; Chinmoyee Borgohain; Utkarsh R. Pandey; Chintan Vedpathak; D. R. Kouli; N. Deori; C. Hassan (Geoheritage, 2024)

Are American electric vehicle owners quitting? - Rubal Dua; Alexander Edwards; Utkarsh Anand; Prateek Bansal (Transportation Research Part D: Transport and Environment, 2024)

Dermorphin [D-Arg2, Lys4] (1-4) Amide Alleviates Frostbite-Induced Pain by Regulating TRP Channel-Mediated Microglial Activation and Neuroinflammation - Obulapathi Ummadisetty; Akhilesh; Anagha Gadepalli; Deepak Chouhan; Utkarsh Patil; Surya Pratap Singh; Sanjay Singh; Vinod Tiwari (Molecular Neurobiology, 2024)

Phenol biodegradation using bio-filter tower packed column with immobilized bacterial consortium: a batch test study - Preeti Sachan; Athar Hussain; Sangeeta Madan; Utkarsh Singh; Manjeeta Priyadarshi (Biodegradation, 2024)

From Waste to Watts-harnessing the power of wastewater to generate bioelectricity - Nishtha Sah; Utkarsh Jain; Nidhi Chauhan (Journal of Water Process Engineering, 2024)

Molecular and serological evidence of chikungunya virus infection with high case fatality among pediatric population with acute encephalitis syndrome: first report from Eastern Uttar Pradesh, India - Pooja Bhardwaj; Kamlesh Sah; Vishal Yadav; Shahzadi Gulafshan; Preeti Dhangur; Utkarsh Srivastava; Gaurav Raj Dwivedi; Manoj Murhekar; Bhupendra Sharma; Rajeev Singh (European Journal of Clinical Microbiology & Infectious Diseases, 2024)

Regression modelling strategies for projected and sustainable kraft pulping of wheat straw - Utkarsh Mishra; Anuj Kumar; Izhar Alam; Chhaya Sharma (Journal of Environmental Management, 2024)

Desert legumes as sustainable sources of proteins and bioactive peptides: Technological insights into functional food development from underutilized plants - Shelly Chauhan; Tripti Joshi; Utkarsh Adhikari; Anagh Sinha; P.R. Deepa; Pankaj Kumar Sharma (Food and Humanity, 2024)

Hypoxia-Induced miR-101 Impairs Endothelial Barrier Integrity Through Altering VE-Cadherin and Claudin-5 - Astha Shukla; Utkarsh Bhardwaj; Apoorva; Pankaj Seth; Sunit K. Singh (Molecular Neurobiology, 2024)

Probabilistic Analysis of Basic Causes of Vessel–Platform Allision Accidents - Utkarsh Bhardwaj; Angelo Palos Teixeira; C. Guedes Soares (Journal of Marine Science and Engineering, 2024)
This paper proposes a methodology to estimate the probability of basic causes of allision accidents between vessels and offshore platforms that overcomes the problem of data scarcity required for causal analysis. The approach uses information derived from incidental data and expert elicitation, processed by a multiple attribute utility method and hierarchical Bayesian analysis. First, the methodology is detailed, briefly describing the adopted approaches. A dataset of allision incidents provided mainly by the UK Health and Safety Executive and other agencies is prepared. The features of the incidents’ causation in terms of the causal factors and basic causes are presented and discussed. A novel scheme is proposed to evaluate the annual occurrence rates of basic causes of accidents from the relative importance of each basic cause derived by the Deck of Cards method. Then, a hierarchical Bayesian analysis is conducted to predict the posterior distribution of the occurrence rate of each basic cause in the time frame under analysis. The proposed holistic methodology provides transparent estimates of allision causation probabilities from limited and heterogeneous datasets.

Influence of calcium depletion and addition on heat stability, buffering capacity, partitioning of minerals and iron binding properties of buffalo milk - Utkarsh Deshmukh; Sumit Arora; Deepika Kathuria; A.K. Singh; Vivek Sharma; Richa Singh (International Dairy Journal, 2024)

Transcriptional regulation of tomato fruit ripening - Priya Gambhir; Utkarsh Raghuvanshi; Rahul Kumar; Arun Kumar Sharma (Physiology and Molecular Biology of Plants, 2024)

Advanced Bioink Materials for Tissue Engineering Applications - Nidhi Chauhan; Kirti Saxena; Rachna Rawal; Utkarsh Jain (Current Tissue Microenvironment Reports, 2024)

Comparative Study of Adsorption, Kinetics, and Thermodynamics of Selected Cationic and Anionic Surfactants on Ultrasound-Assisted Bagasse - Kaman Singh; Utkarsh Dixit; Sudhanshu Mohan (Water, Air, & Soil Pollution, 2024)

Surface activity, mechanisms, kinetics, and thermodynamic study of adsorption of malachite green dye onto sulfuric acid–functionalized Moringa oleifera leaves from aqueous solution - Utkarsh Dixit; Kaman Singh; Sudhanshu Mohan; Alok Kumar Singh; Arun Kumar (Environmental Monitoring and Assessment, 2024)

How useful are mispointing phase SARAL/AltiKa geophysical products for ocean applications? - Suchandra Aich Bhowmick; Aditya Chaudhary; M. Jishad; M. Seemanth; Utkarsh; Neeraj Agarwal; Rashmi Sharma; Honey Gupta; J.V. Thomas; Pascal Bonnefond; J. Verron (Advances in Space Research, 2024)

Phylogenomics-based reclassifications in the genus Psychrobacter including emended descriptions of Psychrobacter pacificensis, Psychrobacter proteolyticus and Psychrobacter submarinus - Jasvinder Kaur; Utkarsh Sood; Chandni Talwar; William B. Whitman; Rup Lal (Antonie van Leeuwenhoek, 2023)

Understanding the Interaction and Potential of Halophytes and Associated Microbiome for Bio-saline Agriculture - Kamlesh K. Meena; Utkarsh Bitla; Ajay M. Sorty; Satish Kumar; Shrvan Kumar; Goraksha C. Wakchaure; Dhananjaya P. Singh; Peter Stougaard; P. Suprasanna (Journal of Plant Growth Regulation, 2023)

Accumulation and effects of persistent organic pollutants and biogeographical solutions: appraisal of global environment - Sneha Mahire; Anupreet Singh Tiwana; Aarif Khan; Pravin M. Nalawade; Gauri Bandekar; Nitu Trehan; Utkarsh Mukkannawar; Simrat Kaur; Vikram Pandit; Pramod N. Kamble (Arabian Journal of Geosciences, 2023)

Surface activity, kinetics, thermodynamics and comparative study of adsorption of selected cationic and anionic dyes onto H3PO4-functionalized bagasse from aqueous stream - Kaman Singh; Utkarsh Dixit; Madhu Lata (Environmental Science and Pollution Research, 2023)

Modelling monthly reference evapotranspiration estimation using machine learning approach in data-scarce North Western Himalaya region (Almora), Uttarakhand - Utkarsh Kumar (Journal of Earth System Science, 2023)

Towards a more accurate characterization of granular media 2.0: Involving AI in the process - Stefano Buitrón Cevallos; Alex X. Jerves; Utkarsh Mital; David A. Medina; V. Santiago Quinteros; Maurizio Mulas; Øyvind Torgersrud (Computers and Geotechnics, 2023)

Era connecting nanotechnology with agricultural sustainability: issues and challenges - Sana Altabbaa; Neharika Ann Mann; Neelam Chauhan; Kumar Utkarsh; Nitika Thakur; Ghada Abd-Elmonsef Mahmoud (Nanotechnology for Environmental Engineering, 2023)

Radiation Oncology Virtual Education Rotation (ROVER) 2.0 for Residents: Implementation and Outcomes - Navjot K. Sandhu; Elham Rahimy; Ryan Hutten; Utkarsh Shukla; Anne Rajkumar-Calkins; Jacob A. Miller; Rie Von Eyben; Christopher R. Deig; Jean-Pierre Obeid; Rachel B. Jimenez; Emma C. Fields; Erqi L. Pollom; et al. (Journal of Cancer Education, 2023)

Simulating hydrological responses using high resolution satellite inputs for a forest dominated hilly catchment of Uttarakhand Himalayas - Utkarsh Kumar; Dhirendra Kumar Singh (Arabian Journal of Geosciences, 2023)

Evaluation of Standardized MODIS-Terra Satellite-Derived Evapotranspiration Using Genetic Algorithm for Better Field Applicability in a Tropical River Basin - Utkarsh Kumar; Rashmi; Ankur Srivastava; Nikul Kumari; Chandranath Chatterjee; Narendra Singh Raghuwanshi (Journal of the Indian Society of Remote Sensing, 2023)

Biochar: a feasible and visible solution for agricultural sustainability - Kumar Utkarsh; Nitika Thakur; Sudheesh K. Shukla (Arabian Journal of Geosciences, 2023)

Spatio-temporal trend and change detection of rainfall for Kosi River basin, Uttarakhand using long-term (115 years) gridded data - Utkarsh Kumar; Dhirendra Kumar Singh; Suresh Chandra Panday; Jaideep Kumar Bisht; Lakshmi Kant (Arabian Journal of Geosciences, 2023)

Freeze v/s air-dried alginate-pectin gel beads modified with sodium dodecyl sulphate for enhanced removal of copper ions - Utkarsh Upadhyay; Sadamanti Sireesha; Sarthak Gupta; I. Sreedhar; K.L. Anitha (Carbohydrate Polymers, 2023)

Seasonal and climatic factors have a significant influence on fertility associated sperm phenomic attributes in crossbred breeding bulls (Bos taurus × Bos indicus) - Utkarsh Kumar Tripathi; Arumugam Kumaresan; Kaustubh Kishor Saraf; Durgesh Murhari Golher; Shivani Chhillar; Samiksha Nayak; Sreela Lathika; Pradeep Nag; Tushar Kumar Mohanty (International Journal of Biometeorology, 2023)

Uncertainty in the Estimation of Partial Safety Factors for Different Steel-Grade Corroded Pipelines - Utkarsh Bhardwaj; Angelo Palos Teixeira; C. Guedes Soares (Journal of Marine Science and Engineering, 2023)
This paper assesses the uncertainty of the partial safety factors for the design of corroded pipelines against burst failure due to the variability associated with the strength model selection. First, 10 calibrated burst pressure prediction models for corroded pipelines are adopted and duly categorised under low-, medium- and high-grade steel classes. The probabilistic characteristics of the pipe burst strength are studied using Monte Carlo simulation for the selected models. Model uncertainty factors are used to correct the burst pressure predictions by the design equations. Model strength factors are derived for models in each category that will provide coherent reliability. The first-order reliability method is employed to estimate the partial safety factors and their uncertainty as a function of operational time. Finally, the influence of the corrosion growth model on the evaluation of partial safety factors is assessed. The results obtained in this study can provide vital guidance regarding the design and maintenance of different steel-grade pipelines.

Economic and environmental analysis of plastics pyrolysis after secondary sortation of mixed plastic waste - Daniel G. Kulas; Ali Zolghadr; Utkarsh S. Chaudhari; David R. Shonnard (Journal of Cleaner Production, 2023)

Discussion of “Procedure for assessing the liquefaction vulnerability of tailings dams” by Ledesma, O, Sfriso, A, and Manzanal, D - David Reid; Simon Dickinson; Riccardo Fanni; Andy Fourie; Utkarsh Mital (Computers and Geotechnics, 2023)

DNA barcoding, an effective tool for species identification: a review - Sandeep Antil; Jeeva Susan Abraham; S. Sripoorna; Swati Maurya; Jyoti Dagar; Seema Makhija; Pooja Bhagat; Renu Gupta; Utkarsh Sood; Rup Lal; Ravi Toteja (Molecular Biology Reports, 2023)

Seismic performance evaluation of masonry infill R.C. frame considering soil-structure interaction - Prajwol Karki; Shuvam Pyakurel; Kumar Utkarsh (Innovative Infrastructure Solutions, 2023)

Adsorptive performance of Tagetes flower waste based adsorbent for crystal violet dye removal from an aqueous solution - Lata Verma; Dipti Sonkar; Chandra Bhan; Jiwan Singh; Utkarsh Kumar; B. C. Yadav; Ashish Nayak (Environmental Sustainability, 2022)

Probabilistic Collapse Design and Safety Assessment of Sandwich Pipelines - Utkarsh Bhardwaj; Angelo Palos Teixeira; C. Guedes Soares (Journal of Marine Science and Engineering, 2022)
This paper presents an approach for probabilistic design and safety assessment of sandwich pipelines under external pressure. The methodology consists of the categorisation of sandwich pipeline collapse strength models based on interlayer adhesion conditions. The models are validated by comparing their predictions against collapse test data of sandwich pipelines. The accuracy of the strength models and their prediction uncertainty are used to select the best model in each category. Regarding interlayer adhesion categories, uncertainty propagation of models’ predictions over a wide range is assessed by the Monte Carlo simulation method. The proposed methodology is demonstrated using a case study of a sandwich pipeline with adequate probabilistic modelling of the basic random variables. Different limit states are defined for three categories of sandwich pipelines, based on which structural reliability indices are estimated. In employing the First Order Reliability Method for sensitivity analysis, the importance of basic variables of the limit states is evaluated. Later, a parametric analysis is conducted, presenting reliability variations for several design and operational scenarios of sandwich pipelines. Finally, to achieve a uniform level of structural reliability of sandwich pipelines, a few suggestions are provided, and practical partial safety factors are calculated. The results of the present analysis can provide guidance on the probabilistic design and operational safety assessment of sandwich pipelines.

Factors driving the tree species richness in sacred groves in Indian subcontinent: a review - Rakesh Kumar; Utkarsh Prajapati; Vijay Kumar Koli (Biodiversity and Conservation, 2022)

Microbial Journey: Mount Everest to Mars - Utkarsh Sood; Gauri Garg Dhingra; Shailly Anand; Princy Hira; Roshan Kumar; Jasvinder Kaur; Mansi Verma; Nirjara Singhvi; Sukanya Lal; Charu Dogra Rawat; Vineet Kumar Singh; Jaspreet Kaur; et al. (Indian Journal of Microbiology, 2022)

Analysis of seasonal variation in surface water quality and water quality index (WQI) of Amba River from Dolvi Region, Maharashtra, India - Ravindra Jaybhaye; Pramod Nandusekar; Manik Awale; Dipen Paul; Uday Kulkarni; Jayesh Jadhav; Utkarsh Mukkannawar; Pramod Kamble (Arabian Journal of Geosciences, 2022)

Optimization of DOTAP/chol Cationic Lipid Nanoparticles for mRNA, pDNA, and Oligonucleotide Delivery - Mengwei Sun; Utkarsh J. Dang; Yuhao Yuan; Alexandra Maria Psaras; Ositomiwa Osipitan; Tracy A. Brooks; Fake Lu; Anthony J. Di Pasqua (AAPS PharmSciTech, 2022)

Plant beneficial effects of Trichoderma spp. suppressing Fusarium wilt and enhancing growth in Tomato - Krishna Kumar; Parika Thakur; Utkarsh Singh Rathore; Sandeep Kumar; R. K. Mishra; N. Amaresan; Sonika Pandey; Monika Mishra (Vegetos, 2022)

Identifying risk factors of intracerebral hemorrhage stability using explainable attention model - Seshasayi Rangaraj; Mobarakol Islam; Vibashan VS; Navodini Wijethilake; Utkarsh Uppal; Angela An Qi See; Jasmine Chan; Michael Lucas James; Nicolas Kon Kam King; Hongliang Ren (Medical & Biological Engineering & Computing, 2022)

Zika Virus NS1 Suppresses VE-Cadherin and Claudin-5 via hsa-miR-101-3p in Human Brain Microvascular Endothelial Cells - Utkarsh Bhardwaj; Sunit K. Singh (Molecular Neurobiology, 2021)

The Alphabet of the Elementary Microbiology: Revisited - Shailly Anand; Sukanya Lal; Utkarsh Sood; Vipin Gupta; Gauri Garg Dhingra; Renu Solanki; Jasvinder Kaur; Roshan Kumar; Anjali Saxena; Ankita Dua; Charu Tripathi; Chandni Talwar; et al. (Indian Journal of Microbiology, 2021)

Evaluation of Indian mustard (Brassica juncea L.) varieties for productivity, profitability, energetics and carbon dynamics under diverse irrigation regimes and sulphur application rates - Kiran Rana; Manoj Parihar; Jitendra Pratap Singh; Rajesh Kumar Singh; Surendra Singh Jatav; Utkarsh Kumar (Environmental Sustainability, 2021)

Adsorptive removal of Cd2+ ions using dolochar at an industrial-scale process optimization by response surface methodology - Utkarsh Upadhyay; Sarthak Gupta; Ankita Agarwal; Inkollu Sreedhar; Kayamkulathethu Latitha Anitha (Environmental Science and Pollution Research, 2021)

Use of meteorological data for identification of agricultural drought in Kumaon region of Uttarakhand - Utkarsh Kumar; Sher Singh; Jaideep Kumar Bisht; Lakshmi Kant (Journal of Earth System Science, 2021)

Evaluation of Spatio-Temporal Evapotranspiration Using Satellite-Based Approach and Lysimeter in the Agriculture Dominated Catchment - Utkarsh Kumar; Ankur Srivastava; Nikul Kumari; Rashmi; Bhabagrahi Sahoo; Chandranath Chatterjee; Narendra Singh Raghuwanshi (Journal of the Indian Society of Remote Sensing, 2021)

Comparative proteomics unravelled the hexachlorocyclohexane (HCH) isomers specific responses in an archetypical HCH degrading bacterium Sphingobium indicum B90A - Monika Sharma; Durgesh Narain Singh; Rohit Budhraja; Utkarsh Sood; Charu Dogra Rawat; Lorenz Adrian; Hans-Hermann Richnow; Yogendra Singh; Ram Krishan Negi; Rup Lal (Environmental Science and Pollution Research, 2021)

Microbial World: Recent Developments in Health, Agriculture and Environmental Sciences - Gauri Garg Dhingra; Anjali Saxena; Aeshna Nigam; Princy Hira; Nirjara Singhvi; Shailly Anand; Jasvinder Kaur; Jaspreet Kaur; Ankita Dua; Vivek Negi; Vipin Gupta; Utkarsh Sood; et al. (Indian Journal of Microbiology, 2021)

A Comparison of Sloth Bear (Melursus ursinus) Diurnal Activity Between Winter and Summer Seasons in Captivity - Utkarsh Prajapati; Vijay Kumar Koli (Proceedings of the Zoological Society, 2020)

Evaluation of Simplified Surface Energy Balance Index (S-SEBI) Method for Estimating Actual Evapotranspiration in Kangsabati Reservoir Command Using Landsat 8 Imagery - Utkarsh Kumar; Bhabagrahi Sahoo; Chandranath Chatterjee; Narendra Singh Raghuwanshi (Journal of the Indian Society of Remote Sensing, 2020)

Better with each throw—a study on calibration and warm-up decrement of real-time consecutive basketball free throws in elite NBA athletes - Ashwin Phatak; Utkarsh Mujumdar; Robert Rein; Fabian Wunderlich; Marc Garnica; Daniel Memmert (German Journal of Exercise and Sport Research, 2020)
Calibration and warm-up decrement seem to influence performance in sensorimotor skills that are repeatedly performed in succession. Current evidence suggests that error rates are greatest for the first of multiple attempts when performing the same sensorimotor task repeatedly. The aim of the present study is, therefore, to study the calibration effect in sets multiple free throws for National Basketball Association (NBA) players by analyzing single, double and triple sets of free throws and their success rates for each of the respective attempts. We hypothesized that the success rate of subsequent free throws is greater compared to immediately preceding throws. To this end, data from the NBA seasons between 2006 and 2016 totaling 610,049 shots and 1098 players were obtained. For a set of double free throws, the success rate of the second throw was greater compared to the first throw. For triple free throws the success rate increased with each successive throw. The results demonstrate differences between consecutive throwing percentages. In conclusion, the current study supports previous findings in darts that calibration effects may explain the underlying increases in performance during repetitive execution of complex sensorimotor skills. Therefore, the present study extends the previous findings to full body movements involving many biomechanical degrees of freedom.

Microbiome: A New Lease to Microbiology - Vipin Gupta; Utkarsh Sood; Roshan Kumar; Rup Lal; Vipin Chandra Kalia (Indian Journal of Microbiology, 2020)

Reconciling Hygiene and Cleanliness: A New Perspective from Human Microbiome - Vipin Gupta; Roshan Kumar; Utkarsh Sood; Nirjara Singhvi (Indian Journal of Microbiology, 2020)

Recent Advancements in the Development of Modern Probiotics for Restoring Human Gut Microbiome Dysbiosis - Roshan Kumar; Utkarsh Sood; Vipin Gupta; Mona Singh; Joy Scaria; Rup Lal (Indian Journal of Microbiology, 2020)

Chicken Gut Microbiome and Human Health: Past Scenarios, Current Perspectives, and Futuristic Applications - Utkarsh Sood; Vipin Gupta; Roshan Kumar; Sukanya Lal; Derek Fawcett; Supriya Rattan; Gerrard Eddy Jai Poinern; Rup Lal (Indian Journal of Microbiology, 2020)

Retraction Note to: In vitro propagation of Canscora decussata Schult. and comparative assessment of anti-cholinesterase and antioxidant capacities of wild-harnessed and in vitro-grown plant extracts - Nitin Kundlikrao Gaikwad; Utkarsh Ravindra Moon; Pratapbhanu Singh Bhadoria; Adinpunya Mitra (Plant Cell, Tissue and Organ Culture (PCTOC), 2019)

Genome Sequencing Revealed the Biotechnological Potential of an Obligate Thermophile Geobacillus thermoleovorans Strain RL Isolated from Hot Water Spring - Durgesh Narain Singh; Utkarsh Sood; Amit Kumar Singh; Vipin Gupta; Mallikarjun Shakarad; Charu Dogra Rawat; Rup Lal (Indian Journal of Microbiology, 2019)

Genome-wide analysis of genes encoding MBD domain-containing proteins from tomato suggest their role in fruit development and abiotic stress responses - Adwaita Prasad Parida; Utkarsh Raghuvanshi; Amit Pareek; Vijendra Singh; Rahul Kumar; Arun Kumar Sharma (Molecular Biology Reports, 2018)

Data modelling for crude oil migration studies using ranking method: a rapid geo-tracer technique for geochemists - Oluwabamise L. Faboya; Oluwadayo O. Sonibare; Olusola T. Faboya; Utkarsh Agrawal; Zewen Liao; O. Ekundayo (Acta Geochimica, 2018)

Influence of season and climatic variables on testicular cytology, semen quality and melatonin concentrations in crossbred bucks reared under subtropical climate - Durgesh Murhari Golher; Arumugam Kumaresan; Kaustubh Kishor Saraf; Shivani Chhillar; Samiksha Nayak; Utkarsh K Tripathi; Chavan Nitin Bhaskar; Surender Singh Lathwal; Tushar Kumar Mohanty (International Journal of Biometeorology, 2018)

Identification of Novel Abiotic Stress Proteins in Triticum aestivum Through Functional Annotation of Hypothetical Proteins - Saurabh Gupta; Yashbir Singh; Himansu Kumar; Utkarsh Raj; A. R. Rao; Pritish Kumar Varadwaj (Interdisciplinary Sciences: Computational Life Sciences, 2018)

Infection and Microbiome: Impact of Tuberculosis on Human Gut Microbiome of Indian Cohort - Utkarsh Sood; Abhay Bajaj; Roshan Kumar; Sachin Khurana; Vipin Chandra Kalia (Indian Journal of Microbiology, 2018)

Microbial taxonomy in the era of OMICS: application of DNA sequences, computational tools and techniques - Nitish Kumar Mahato; Vipin Gupta; Priya Singh; Rashmi Kumari; Helianthous Verma; Charu Tripathi; Pooja Rani; Anukriti Sharma; Nirjara Singhvi; Utkarsh Sood; Princy Hira; Puneet Kohli; et al. (Antonie van Leeuwenhoek, 2017)

Identification of Dual Natural Inhibitors for Chronic Myeloid Leukemia by Virtual Screening, Molecular Dynamics Simulation and ADMET Analysis - Himansu Kumar; Utkarsh Raj; Swati Srivastava; Saurabh Gupta; Pritish K. Varadwaj (Interdisciplinary Sciences: Computational Life Sciences, 2016)

A mechanistic insight into hydrogen peroxide-mediated elicitation of bioactive xanthones in Hoppea fastigiata shoot cultures - Utkarsh Ravindra Moon; Adinpunya Mitra (Planta, 2016)

Erratum to: Flavonoids as Multi-Target Inhibitors for Proteins Associated with Ebola Virus: In Silico Discovery Using Virtual Screening and Molecular Docking Studies - Utkarsh Raj; Pritish Kumar Varadwaj (Interdisciplinary Sciences: Computational Life Sciences, 2016)

Flavonoids as Multi-target Inhibitors for Proteins Associated with Ebola Virus: In Silico Discovery Using Virtual Screening and Molecular Docking Studies - Utkarsh Raj; Pritish Kumar Varadwaj (Interdisciplinary Sciences: Computational Life Sciences, 2016)

Biomarkers of oxidative stress in rat for assessing toxicological effects of heavy metal pollution in river water - Utkarsh A. Reddy; P. V. Prabhakar; G. Sankara Rao; Pasham Rajasekhar Rao; K. Sandeep; M. F. Rahman; S. Indu Kumari; Paramjit Grover; Haseeb A. Khan; M. Mahboob (Environmental Science and Pollution Research, 2015)

RETRACTED ARTICLE: In vitro propagation of Canscora decussata Schult. and comparative assessment of anti-cholinesterase and antioxidant capacities of wild-harnessed and in vitro-grown plant extracts - Nitin Kundlikrao Gaikwad; Utkarsh Ravindra Moon; Pratapbhanu Singh Bhadoria; Adinpunya Mitra (Plant Cell, Tissue and Organ Culture (PCTOC), 2015)

Shoot cultures of Hoppea fastigiata (Griseb.) C.B. Clarke as potential source of neuroprotective xanthones - Utkarsh Ravindra Moon; Debabrata Sircar; Ritu Barthwal; Sukanta Kumar Sen; Till Beuerle; Ludger Beerhues; Adinpunya Mitra (Journal of Natural Medicines, 2015)

Flavonoids as multi-target inhibitors for proteins associated with Ebola virus: in-silico discovery using virtual screening and molecular docking studies - Utkarsh Raj; Pritish Kumar Varadwaj (Interdisciplinary Sciences: Computational Life Sciences, 2015)

The in vitro antioxidant capacities of Polianthes tuberosa L. flower extracts - Saborni Maiti; Utkarsh Ravindra Moon; Paramita Bera; Tanmoy Samanta; Adinpunya Mitra (Acta Physiologiae Plantarum, 2014)

CYP2A6 genetic variation and dexmedetomidine disposition - Utkarsh Kohli; Pratik Pandharipande; Mordechai Muszkat; Gbenga G. Sofowora; Eitan A. Friedman; Mika Scheinin; Alastair J. J. Wood; E. Wesley Ely; Rachel F. Tyndale; Leena Choi; C. Michael Stein; Daniel Kurnik (European Journal of Clinical Pharmacology, 2012)

A Bayesian hierarchical nonlinear mixture model in the presence of artifactual outliers in a population pharmacokinetic study - Leena Choi; Brian S. Caffo; Utkarsh Kohli; Pratik Pandharipande; Daniel Kurnik; E. Wesley Ely; C. Michael Stein (Journal of Pharmacokinetics and Pharmacodynamics, 2011)

Landscape Ecological Planning Through a Multi-Scale Characterization of Pattern: Studies in the Western Ghats, South India - Harini Nagendra; Ghate Utkarsh (Environmental Monitoring and Assessment, 2003)